Vpliv izkustva ob živih živalih v razredu na učenčevo poznavanje živali in njihovih lastnosti - Lačen, Iztok; Fošnarič, Samo (Revija za elementarno izobraževanje, 2009)
Experiencing live animals in the classroom and their influence on pupils’ knowledge of animals. When studying the environment, teachers are often conscious of the fact that nature is the best source of obtaining information. With this in mind, teachers often decide to observe live animals by bringing them or keeping them in the classroom, particularly for classes that concern living beings. Lately, a lot of research has been done on this topic and it has shown that these animals have a positive influence on children. For this reason our research deals with the question of whether the presence of live animals in the classroom really enhances knowledge about these animals. In order to study this we carried out research on 110 primary school children. 68 of these children were included in experiments that involved working with live animals. We determined the amount of knowledge these students received by preparing special questionnaires that were filled out in two phases: before and after contact with the live animals. The results our research show and confirm that the students who work with live animals in the classroom learn more than students who have had no such experience, which is in accordance with the known facts concerning this topic.